Employability profile of the Peruvian public accountant - Tarazona, Silvia (2003)
The traditional perspective on the Public Accountant's professional services is running out of time and, although such services are still valuable for enterprises, the survival of the latter demands a more open and aggressive professional attitude in this field (Lebrija, 1998). Employability profiles respond to this demand by acknowledging the new abilities required of the labor force, which go beyond professional competencies. It is also these profiles which will allow coping with employment instability and difficulties produced by the combined stream of worldwide economic integration and technological developments, as stated by the International Office of Labor (1998). This research intends to be a preliminary approach to the Public Accountant's Employability Profile, as required by industrial and service enterprises, which is expressed in terms of the abilities acknowledged by an international employability profile.